Cross-amplification of heterologous microsatellite markers in Rhamdia quelen and Leporinus elongatus - Lopera-Barrero, Nelson Mauricio; Tanamati, Fernanda [UNESP]; Del Pilar Rodriguez-Rodriguez, Maria; Povh, Jayme Aparecido; Poveda-Parra, Angela Rocio; Otonel, Rodrigo Alejandro Arellano; De Castro, Pedro Luiz; Dos Reis Goes, Elenice Souza; Furlan, Pâmela Juliana; Ribeiro, Ricardo Pereira (Universidade Estadual de Londrina, 2016)
Native fish species in Brazil are an asset in fish farming, but their natural stocks have been significantly reduced in recent years. To mitigate this negative impact, studies on fish conservation are being conducted and genetic tools for the discrimination of population parameters are increasingly achieving great importance. Current analysis evaluates a set of microsatellite heterologous primers in the jundiá (Rhamdia quelen) and in the piapara (Leporinus elongatus). Samples from the caudal fin of 15 broodstock from each species were analyzed. DNA extraction was performed with NaCl protocol and the integrity of the extracted DNA was checked with agarose gel 1%. Twenty primers developed for Piaractus mesopotamicus, Colossoma macropomum, Prochilodus lineatus, Brycon opalinus and Oreochromis niloticus were evaluated. Cross amplification of four primers of the B. opalinus and P. lineatus species (BoM12, Pli43 and Pli60 in R. quelen and BoM2, Pli43 and Pli60 in L. elongatus) was assessed. Primers of P. mesopotamicus, C. macropomum and O. niloticus showed no cross amplification in the two species analyzed. Results revealed the possibility of using the four amplified heterologous primers in genetic studies for R. quelen and L. elongatus.
Keywords: Heterologous primers; Jundiá; Piapara